Overexpression of cytosolic long noncoding RNA cytb protects against pressure-overload-induced heart failure via sponging microRNA-103-3p - Xudong Zhang; Shuai Yuan; Jingbo Liu; Yuyan Tang; Yan Wang; Jiabing Zhan; Jiahui Fan; Xiang Nie; Yanru Zhao; Zheng Wen; Huaping Li; Chen Chen; et al. (Elsevier, 2022)
Long noncoding RNAs (lncRNAs) play crucial roles in cardiovascular diseases. To date, only limited studies have reported the role of mitochondria-derived lncRNAs in heart failure (HF). In the current study, recombinant adeno-associated virus 9 was used to manipulate lncRNA cytb (lnccytb) expression in vivo. Fluorescence in situ hybridization (FISH) assay was used to determine the location of lnccytb, while microRNA (miRNA) sequencing and bioinformatics analyses were applied to identify the downstream targets. The competitive endogenous RNA (ceRNA) function of lnccytb was evaluated by biotin-coupled miRNA pull-down assays and luciferase reporter assays. Results showed that lnccytb expression was decreased in the heart of mice with transverse aortic constriction (TAC), as well as in the heart and plasma of patients with HF. FISH assay and absolute RNA quantification via real-time reverse transcription PCR suggested that the reduction of the lnccytb transcripts mainly occurred in the cytosol. Upregulation of cytosolic lnccytb attenuated cardiac dysfunction in TAC mice. Moreover, overexpression of cytosolic lnccytb in cardiomyocytes alleviated isoprenaline-induced reactive oxidative species (ROS) production and hypertrophy. Mechanistically, lnccytb acted as a ceRNA via sponging miR-103-3p, ultimately mitigating the suppression of PTEN by miR-103-3p. In summary, we demonstrated that the overexpression of cytosolic lnccytb could ameliorate HF.